Stała Współpraca Strukturalna (PESCO) jako przykład dyferencjalizmu eksperymentalnego w Unii Europejskiej (Politeja, 2024)
POLAND IN THE EUROPEAN UNION TOWARDS EUROSCEPTIC SELF-ISOLATIONBy joining the European Union on 1 May 2004, Poland symbolically finalized the transformation process from the position of a nation state (NS) towards a member state (MS). The European Union Member States, in addition to being the main actors of the integration process, are also affected by various natural centrifugal forces in this atypical international organization. It results from selfishness and particularism of the states as well as from natural national selfinterests, on which stable national preferences are clearly defined and exposed by member states. From the perspective of the transformation process of Poland as the largest and most important EU member state located in Central and Eastern Europe, we can distinguish two periods: 1. 2004-2015. At that time, Poland strongly supported the European Commission (EC) and the Community method, which gives the EC a central role in the decision-making process. This period can be defined by the process of transition from a nation state to a Member State. 2. From 2015, when Poland was ruled by anti-liberal and more Eurosceptic government. This period, in turn, can be defined by the hybrid accumulation of features of a national state and a Member State, which makes us deal with a national member state (NMS). However, the tendency that can be observed runs in the direction of a backward transformation from a Member State to a nation-state. The subject of this study is only the second period in the European policy of Poland expressed by the accumulation of the features of NS and MS with a tendency in the reverse direction of transformation from a Member State to a nation- state. The main research thesis focuses on the statement that after 2015 Poland in the European Union drifts towards Eurosceptic self-isolation.